2020
DOI: 10.1038/s41586-020-2733-7
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven post-translational installation of reactive protein side chains

Abstract: Post-translational modifications (PTMs) greatly expand the structures and functions of proteins in nature 1,2 . Although synthetic protein functionalization strategies allow mimicry of PTMs 3,4 , as well as formation of unnatural protein variants with diverse potential functions, including drug carrying 5 , tracking, imaging 6 and partner crosslinking 7 , the range of functional groups that can be introduced remains limited. Here we describe the visible-light-driven installation of side chains at dehydroalanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 57 publications
3
169
0
Order By: Relevance
“…88 In 2020, Davis and Gouverneur reported for the first time a protocol enabling precise incorporation of a CF 2 H group on a protein (Scheme 30F). 134 2-PySO 2 CF 2 H was employed to release a CF 2 H radical capable of reacting at the terminal carbon of a SOMOphilic dehydroalanine (Dha) residue. The reaction is performed at ambient and biocompatible conditions, allowing for the preparation of hydrodifluoromethylated proteins in high yields (up to quantitative) and short reaction times.…”
Section: C(sp 3 )-Cf 2 H Bond Formation: Radical Difluoromethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…88 In 2020, Davis and Gouverneur reported for the first time a protocol enabling precise incorporation of a CF 2 H group on a protein (Scheme 30F). 134 2-PySO 2 CF 2 H was employed to release a CF 2 H radical capable of reacting at the terminal carbon of a SOMOphilic dehydroalanine (Dha) residue. The reaction is performed at ambient and biocompatible conditions, allowing for the preparation of hydrodifluoromethylated proteins in high yields (up to quantitative) and short reaction times.…”
Section: C(sp 3 )-Cf 2 H Bond Formation: Radical Difluoromethylationmentioning
confidence: 99%
“…Seminal work in this direction has recently been reported by Davis, Gouverneur and co-workers, who developed site-selective photocatalytic hydrodifluoromethylation and difluoromethylation of dehydroalanine and tryptophan residues in proteins, respectively. 99,134…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The CÀ C bond forming reaction are initiated by photocatalyzed radical formation, a reaction manifold that is compatible with the aqueous environment required for proteins and thereby underpins its tremendous utility. [67] Additionally, organoborates have also been used to functionalize complex antibiotic peptides (thiostrepton and nisin) at Dha and dehydrobutyrine (Dhb) residues. [68] A highly watersoluble analog of [Ir(dF(CF 3 )ppy) 2 (dtbbpy)]PF 6 with quaternary ammonium in lieu of the t Bu groups allowed peptide and protein modification with low reagent and catalyst loading in physiologically relevant conditions.…”
Section: Bioconjugationmentioning
confidence: 99%
“…Another recent study reported the photochemical generation of carbon radicals using visible light that subsequently reacted with Dha residues selectively. 48 The technique demonstrated broad applicability, with the synthesis of over 50 novel side chains bearing a variety of different functionalities on diverse protein scaffolds.…”
Section: Dehydroamino Acid Synthetic Biologymentioning
confidence: 99%